The Potential of Bacillus sp. and FOBIO Biopesticide with Mustard Greens (Brassica rapa L. var. parachinensis) as Bioremediation Agents for Cadmium - Dykha Maretha Setyawan; Endang Tri Wahyu Prasetyawati; Sri Wiyatiningsih (The University of Lampung, 2026)
Cadmium (Cd) contamination in agricultural land due to excessive use of fertilizers and pesticides has detrimental effects on soil quality, plant growth, and human health. Bioremediation offers a simple and environmentally friendly approach to address this issue. This study aimed to evaluate the potential of Bacillus sp., FOBIO biopesticide, and green mustard (Brassica rapa L. var. parachinensis) as bioremediation agents for Cd-contaminated soil. The experiment was conducted using a Completely Randomized Design (CRD) with seven treatments and four replications. Observed parameters included Cd concentration in the soil before and after remediation, as well as the growth and physiological responses of mustard plants. The application of FOBIO biopesticide without plants resulted in the highest Cd reduction (4.57 mg/kg), while the combination of Bacillus sp. and mustard plants reduced Cd by 4.11 mg/kg, and mustard plants alone reduced Cd by 2.40 mg/kg, outperforming the control. FOBIO biopesticide application significantly enhanced leaf number, plant height, and fresh weight compared to other treatments. These findings indicate that Bacillus sp., FOBIO biopesticide, and green mustard have strong potential as bioremediation agents for Cd-contaminated soils.